PENGAWASAN SATUAN POLISI PAMONG PRAJA TERHADAP USAHA WARUNG INTERNET DI KECAMATAN TAMPAN TAHUN 2018 - Aryani, Anggi; Tinov, M. Y. Tiyas (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
The Civil Service Police Unit is a Regional Government apparatus in Peace and Public Order and enforcing Regional Regulations. The Pamong Praja police unit has the duty to supervise general freedoms, one of which is an internet cafe business in Pekanbaru City. Tampan Sub-district is a sub-district that has the highest number of internet cafes compared to 12 other sub-districts in Pekanbaru City. This research was conducted at the City Civil Service Police Unit in Pekanbaru City. The importance of the role of the Pekanbaru City Civil Service Police Unit in the internet shop business so that the operation of internet shop business owners participate in the standardization prepared by the Government.            The purpose of this study was to study the supervision of the Pekanbaru City Civil Service Police Unit on the stall business in Tampan District in 2018 and the factors influencing the supervision.            The theoretical concept used by the writer is the process of supervision. This type of research is a qualitative descriptive. The technique of collecting data is done through in-depth interviews with informants selected purposively and recording documents. Data analysis techniques using descriptive analysis method.            The observation of the Pekanbaru City Civil Service Police Unit on the internet shop business in Tampan District has not been running optimally. Pekanbaru City Pamog Praja Police Unit against internet cafe business is the number of supervisors that are still inadequate, facilities such as operational vehicles that are still lacking to conduct surveillance and supervision systems that are still not routine and are not suitable for supervision.    Keywords: Supervision, Internet Cafes, Tampan District.